Say x is 1 1^2=1 4x=4 4*1=4 I believe that is what you were asking
Answer:
14.14 i hope this helps lol ;)
Step-by-step explanation:
We have
![125 - x {}^{3}](https://tex.z-dn.net/?f=125%20-%20x%20%7B%7D%5E%7B3%7D%20)
First, 125 is a perfect cube because
![5 \times 5 \times 5 = 125](https://tex.z-dn.net/?f=5%20%5Ctimes%205%20%5Ctimes%205%20%3D%20125)
and
x^3 is a perfect cube because
![x \times x \times x = x {}^{3}](https://tex.z-dn.net/?f=x%20%5Ctimes%20%20x%20%5Ctimes%20x%20%3D%20x%20%7B%7D%5E%7B3%7D%20)
so we can use the difference of cubes identity
![( {x}^{3} - {y}^{3} ) = (x - y)( {x}^{2} + xy + {y}^{2} )](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B3%7D%20%20-%20%20%7By%7D%5E%7B3%7D%20%29%20%3D%20%28x%20-%20y%29%28%20%7Bx%7D%5E%7B2%7D%20%20%2B%20xy%20%2B%20%20%7By%7D%5E%7B2%7D%20%29)
Let say we have two perfect cubes:
64 because 8×8×8=64
and 27 because 3×3×3=27 and let subtract
![64 - 27](https://tex.z-dn.net/?f=64%20-%2027)
we know that
![64 - 27 = 37](https://tex.z-dn.net/?f=64%20-%2027%20%3D%2037)
but using the difference of cubes identity we should get the same thing.
Remeber cube root of 64 is 4 and cube root of 27 is 3 so we have
![(4 - 3)( {4}^{2} + 4(3) + 3 {}^{2} )](https://tex.z-dn.net/?f=%284%20-%203%29%28%20%7B4%7D%5E%7B2%7D%20%20%2B%204%283%29%20%2B%203%20%7B%7D%5E%7B2%7D%20%29)
![1(16 + 12 + 9) = 1(37) = 37](https://tex.z-dn.net/?f=1%2816%20%2B%2012%20%2B%209%29%20%3D%201%2837%29%20%3D%2037)
So the difference of cubes works for real numbers. This is a good way to help remeber the identity using real numbers.
Back on to the topic,
we know that 5 is cube root of 125 and x is the cube root of x^3 so we have
![(5 - x)( {5}^{2} + 5x + {x}^{2} ) =](https://tex.z-dn.net/?f=%285%20-%20x%29%28%20%7B5%7D%5E%7B2%7D%20%20%2B%205x%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%29%20%3D%20)
![(5 - x)(25 + 5x + {x}^{2} )](https://tex.z-dn.net/?f=%285%20-%20x%29%2825%20%2B%205x%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%29)
Answer:
-7/3
Step-by-step explanation:
2(6−4)=3(6+2)
2(6x-4)=3(6x+2)
Solve
1
Distribute
2(6−4)=3(6+2)
{\color{#c92786}{2(6x-4)}}=3(6x+2)
12−8=3(6+2)
{\color{#c92786}{12x-8}}=3(6x+2)
2
Distribute
12−8=3(6+2)
12x-8={\color{#c92786}{3(6x+2)}}
12−8=18+6
12x-8={\color{#c92786}{18x+6}}
3
Add
8
8
to both sides of the equation
12−8=18+6
12x-8=18x+6
12−8+8=18+6+8
12x-8+{\color{#c92786}{8}}=18x+6+{\color{#c92786}{8}}
5 more steps
Solution
=−7/3
I think it’s a loyalty marking program. I think it’s that because I feel like it’s the only answer that really makes sense bc the customer is being loyal to the service in order to receive their “reward”